Effects of low intensity laser in in vitro bacterial culture and in vivo infected wounds - Pereira,Pâmela Rosa (2014)
OBJECTIVE: to compare the effects of low intensity laser therapy on in vitro bacterial growth and in vivo in infected wounds, and to analyze the effectiveness of the AsGa Laser technology in in vivo wound infections. METHODS: in vitro: Staphylococcus aureus were incubated on blood agar plates, half of them being irradiated with 904 nm wavelength laser and dose of 3J/cm2 daily for seven days. In vivo: 32 male Wistar rats were divided into control group (uninfected) and Experimental Group (Infected). Half of the animals had their wounds irradiated. RESULTS: in vitro: there was no statistically significant variation between the experimental groups as for the source plates and the derived ones (p>0.05). In vivo: there was a significant increase in the deposition of type I and III collagen in the wounds of the infected and irradiated animals when assessed on the fourth day of the experiment (p=0.034). CONCLUSION: low-intensity Laser Therapy applied with a wavelength of 904nm and dose 3J/cm2 did not alter the in vitro growth of S. aureus in experimental groups; in vivo, however, it showed significant increase in the deposition of type I and III collagen in the wound of infected and irradiated animals on the fourth day of the experiment.